Spanish education in words: a text mining experience: A linguistic diachronic study of educational laws with R - Florio, Nicola (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Words play an essential role in all areas of communication, but particularly in the case of educational laws, words become a vehicle for conveying ideas and values. Following the principles of text mining and with the help of the R Studio tool, the aim of this article is to analyze the use of language in these legislative texts to transmit certain priorities in the field of education. The result is a diachronic study of the linguistic evolution perceived in Spanish educational laws from 1980 to 2022.